Policy on the Development of Innovation Clusters in the EU. Conclusions and Tasks for Ukraine - Salikhov, M. M. (Statistics of Ukraine, 2025)
The article demonstrates that since the early 2000s, the EU’s cluster policy has transformed into one of the key instruments for achieving the strategic goals of the European Union. It has been established that the creation of clusters was embedded in the Lisbon Strategy and, since 2006, received formal regulatory recognition in the official documents of the European Commission. It has been identified that, thanks to the establishment of a High-Level Advisory Group, the foundations of a general cluster development policy within the EU were formed (which became the basis for the introduction of corresponding national policies), as well as specialized platforms and support mechanisms were launched.The study establishes that in EU documents clusters are considered a tool for enhancing the socio-economic stability of regions (in particular through the implementation of smart specialization strategies), increasing industrial competitiveness, stimulating innovation in small and medium-sized enterprises, and forming transnational value chains. It is concluded that the EU's cluster policy has a complex, cross-sectoral character, combining not only the instruments of innovation, industrial, and regional policies, but also those of other policy areas.Based on the analysis of the EU experience, the following proposals are made: to establish a national-level expert group on cluster policy for developing the conceptual foundations of building a cluster ecosystem in Ukraine; to take measures to ensure coordinated actions among central executive authorities regarding the creation, functioning, and support of clusters within the framework of relevant policies; to designate the development of innovation clusters as a priority of state cluster policy (their development directions should correspond to the priority areas of innovation activity defined by Ukrainian legislation); to launch a budget program for providing state aid to such clusters; and to introduce tools to encourage the internationalisation of Ukrainian innovation clusters, in particular by creating cross-border partnerships with European clusters, research institutions, and businesses aimed at solving common problems under current challenges and threats.